Pemanfaatan Sumber Karbohidrat Yang Berbeda (Umbi Suweg, Umbi Talas, Dan Umbi Kimpul) Sebagai Substitusi Media Na (Nutrient Agar) Untuk Pertumbuhan Bakteri - Purwati, Suci (2016)
Instant media are difficult to obtain and relatively high prices encourage researchers to make a substitution media with materials that are cheap and easily. This studyaims to determinethe useof differentcarbohydrate sourcesassubstitutesmediaNutrientAgar (NA) forbacterial growth. Thisresearchusingcompletely randomized design(CRD) twofactors.The first factoris a typeof bacteriaisEscherichiacoliandStaphylococcusaureusandsecond is theAmorphophallus campanulatus, Colocasia esculenta, andXanthosoma violaceum. Inoculatedwith thetest bacteriaspreadplatemethodandincubatedat 37 °C for 24 hoursfor thebacteria inmediaNutrientagar and48 hourson mediumtubers.Parametersmeasured werethe number ofpopulationandthe size ofbacterial colonies.In Escherichiacoli, the highestpopulationon themediaof theAmorphophallus campanulatus (4.6 x 109CFU/ml), nutrient agar medium(3.6 x 109CFU/ml), Xanthosoma violaceum (3.5 x109CFU/ml), than the last Colocasia esculenta (2.8 x 109CFU/ml), while thehighestpopulation ofStaphylococcus aureuson theAmorphophallus campanulatus (8.2 x 109CFU/ml), nutrient agarmedia(5.5 x 109CFU/ml), Colocasia esculenta (3, 4x 109CFU/ml), and the last Xanthosoma violaceum (2.3 x 109CFU/ml). Based onthe size of thebacterial colonies, ofthe threemediatubersobtainsmallcolonybuta lot. The conclusion ofthis studymediathat can be usedas asubstitutenutrient agarmedium, ismediaofAmorphophallus campanulatus.